Analysis Of Profitability, Funding Decisions, Company Size And Capital Structure On The Financial Performance Of p Companies Listed On The Indonesian Stock Exchange - Siti Aminah; Septa Diana Nabella; Dewi Permata Sari; Andi Hidayatul Fadlilah; Ita Mustika; Maya Richmayati (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze and test profitability, funding decisions, company size and capital structure on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022. The methodology in this research is to use relevant data. This research was conducted using secondary data and data collection techniques with financial report analysis, in the form of annual reports published via the internet via the site www.idx.co.id. Using SPSS to assess the financial performance of manufacturing companies. The research results show that partially company size has a significant effect on 0.025 ≤ 0.05 financial performance, profitability has no significant effect on financial performance, funding decisions and capital structure have no significant effect on financial performance. This research is very important to achieve good financial management in increasing profitability, funding decisions, company size, and capital structure in its financial strategy to achieve optimal financial performance.